APLIKASI PENGENALAN LINGKUNGAN FAKULTAS ILMU KOMPUTER UPNVJ DENGAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Cahyo Adi Lukito (2023)
The tech development nowadays moving so fast. Including multimedia and education sector. Virtual reality now become so popular. One of virtual reality fields is augmented reality that can show virtual object to real world. This augmented reality can be used by many business section, including education sector. Augmented reality can be an innovation to create interactive education, so that learning can be easier to be understood. Augmented reality implementation to introduction to the campus environment can be a solution to overcome online learning that prevent student to come to the campus in this COVID-19 pandemic. This implementation can be realized with an Android-based app. Android-based app chosen because the user is wider than any mobile operating system. One of the tool to create this app is with Unity software. With this augmented reality app, researcher hope that this app can be utilized as one of learning medias to students, especially students of Computer Science Faculty of UPNVJ, which not familiar with the environment in campus.